Impact of endocrine dysregulation on disability and non-motor symptoms in pediatric onset multiple sclerosis - Abe, Justin; Jafarpour, Saba; Vu, My H.; O'Brien, Devon; Boyd, Natalie K.; Vogel, Benjamin N.; Nguyen, Lina; Paulsen, Kelli C.; Saucier, Laura E.; Ahsan, Nusrat; Mitchell, Wendy G.; Santoro, Jonathan D. (Frontiers in Neurology, 2023)
Background Pediatric onset multiple sclerosis (POMS) commonly occurs at the time of various endocrine changes. Evaluation of the impact of endocrine status on disease severity in POMS has not been previously explored. Objective This study sought to evaluate if sex and stress hormones in children with POMS impact motor and non-motor diseases severity. Methods A single-center case control study was performed. Individuals with POMS were compared to individuals without neurologic disease. Each individual had three blood draws assessing stress and sex hormones between 07:00 and 09:00. Measures of fatigue (Epworth sleepiness scale), depression (PHQ-9), and quality of life (PedsQL) assessed at each visit. Results Forty individuals with POMS and 40 controls were enrolled. Individuals with POMS had lower free testosterone (p = 0.003), cortisol (p < 0.001), and ACTH (p < 0.001) and had higher progesterone (p = 0.025) levels than controls. Relapses and EDSS were not impacted by endocrine variables. The POMS cohort had a significantly higher Epworth score (p < 0.001), PHQ-9 score (p < 0.001), and lower PQL score (p < 0.001) than controls. Non-motor measures were not associated with endocrine status. Conclusion Free testosterone, cortisol, ACTH, and progesterone were abnormal in children with POMS although there was no association between endocrine status and markers of disease severity or non-motor symptoms of MS.